Masters of drawing - Pini, Margherita (Florence, Italy : Scala, 2010)
The book intends to show the main stages of drawing history from the beginning of 20th century, with particular regard to European development. Through a large selection of images, the reader is introduced to the knowledge of the most important artistic schools which used drawing as part of their preparation and training for young artists. The reader is also introduced to fundamental graphic techniques and of the classifications that define thevaried areas and types of drawing.
Drawing.
Text in : English, German, Dutch and Spanish.
Keywords: Drawing, European -- History; Drawing